2020
DOI: 10.1111/jace.17457
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of GDC cathodic functional thin films for oxide ion incorporation enhancement

Abstract: In this paper, we report successful fabrication of a gadolinia-doped ceria (GDC) thin film using atomic layer deposition (ALD) for improving the performance of solid oxide fuel cells (SOFCs). By varying the deposition conditions and adjusting the configuration of the ALD supercycle, the doping ratio of ALD GDC was controlled. The morphology, crystallinity, and chemical composition of ALD GDC thin films were analyzed. ALD GDC showed different surface chemistry, including oxidation states, at different doping ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Therefore, even further performance enhancement is expected if electrode modifications are applied. It is also noteworthy that only a limited number of reported AAO-supported SOFCs have achieved higher performance than the one reported in this study, and they all have been achieved through utilizing more complex electrode materials or employing additional chemical vapor deposition processes. , Specifically for all-sputtered TF-SOFCs, Yu et al reported 477 mW/cm 2 at 500 °C with a nanostructure-tailored Ni anode (Ni/GDC/YSZ/GDC/Pt cell configuration). Ren et al reported 480 mW/cm 2 at 500 °C with a Ni–YSZ/YSZ/GDC/LSC-GDC cell by adjusting the cosputtering conditions for the LSC-GDC cathode.…”
Section: Resultsmentioning
confidence: 70%
“…Therefore, even further performance enhancement is expected if electrode modifications are applied. It is also noteworthy that only a limited number of reported AAO-supported SOFCs have achieved higher performance than the one reported in this study, and they all have been achieved through utilizing more complex electrode materials or employing additional chemical vapor deposition processes. , Specifically for all-sputtered TF-SOFCs, Yu et al reported 477 mW/cm 2 at 500 °C with a nanostructure-tailored Ni anode (Ni/GDC/YSZ/GDC/Pt cell configuration). Ren et al reported 480 mW/cm 2 at 500 °C with a Ni–YSZ/YSZ/GDC/LSC-GDC cell by adjusting the cosputtering conditions for the LSC-GDC cathode.…”
Section: Resultsmentioning
confidence: 70%
“…5e ). 39 The optimal performance was achieved when 18.8 mol% of Gd-doped ceria was inserted as an inter-layer, and power density of 288.24 mW cm −2 was obtained with three times greater performance at 450 °C ( Fig. 5f ).…”
Section: Ald For Thin Film Electrolytesmentioning
confidence: 94%
“…In the same manner, studies aiming to enhance SOFC performance outcomes by improving the electrode-electrolyte interface property by inserting a very thin inter-layer with various compositions between the electrode and electrolyte are ongoing. [38][39][40] Recently, Kim et al deposited various compositions of gadolinia-doped ceria (GDC, Gd 2 O 3 doping ratio: 11.9 mol%, 13.9 mol%, 18.8 mol%, and 25.2 mol%) onto the interface of YSZ and a Pt electrode and measured the peak power density (Fig. 5e).…”
Section: Ald For Thin Film Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution focuses on utilizing highly active component materials, starting with electrode materials of higher catalytic activity or electrolytes of higher ionic conductivity. However, the selection of SOFC component materials that reduce temperature while remaining cost-effective is quite limited [169,170]. Alternatively, temperature reduction can be achieved through improvements in manufacturing processes, such as nanostructured components and thin-film electrolytes [171,172].…”
Section: Options To Decrease the Operating Temperature Of Sofcmentioning
confidence: 99%